Odpowiedź :
Obliczenia :
[tex]c] \ (8^7)^8:(8^8)^5=8^{7\cdot8}:8^{8\cdot5}=8^{56}:8^{40}=8^{56-40}=8^{16}\\\\d] \ \frac{(a^4)^2\cdot a^0\cdot a^9}{a^{10}:a^8}=\frac{a^{4\cdot2}\cdot a^0\cdot a^9}{a^{10}:a^8}=\frac{a^8\cdot a^0\cdot a^9}{a^{10}:a^8}=\frac{a^{8+0+9}}{a^{10-8}}=\frac{a^{17}}{a^2}=a^{17-2}=a^{15}[/tex]
Odpowiedź:
c)(8⁷)⁸:(8⁸)⁵=8⁵⁶-8⁴⁰=8⁵⁶⁻⁴⁰=8¹⁶
d)[tex]\frac{(a^4)^2*a^0*a^9}{a^{10}:a^8} =\frac{a^8*1*a^9}{a^{10-8}} =\frac{a^{8+9}}{a^2} =a^{17-2}}=a^{15}}[/tex]
Szczegółowe wyjaśnienie: